PENGEMBANGAN BRANDING DAN KOMUNIKASI VISUAL UMKM KEDAI NITA - Irena, Lydia; Michelle Augustine (Jurnal Serina Abdimas, 2025)
The rapid development of digital technology presents new challenges for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in their ability to adapt to modern marketing strategies. One of these challenges is the lack of understanding regarding the importance of branding and visual communication as tools for building a strong image and enhancing business competitiveness. Kedai Nita, an MSME located in South Jakarta, is one such business that has yet to implement branding strategies effectively due to limitations in visual design and technology. This Community Service Activity aims to assist the partner in developing a brand identity through the creation of a comprehensive brand guideline tailored to the characteristics of the business. The implementation method is divided into three stages: pre-activity (audience engagement and needs analysis), implementation (assistance in developing the brand guideline), and post-activity (evaluation, reporting, and dissemination of results). This initiative not only provides practical solutions for the partner but also serves as a means of knowledge transfer from academics to MSME practitioners. It is expected that the outcome of this activity will improve visual literacy and branding competence among MSMEs, thereby strengthening their position in facing increasingly competitive market conditions in the digital era. The results of the Community Service Activity activities indicate that the consistent application of visual elements across various media—such as packaging, signage, and digital platforms—has a significant impact on brand cohesiveness. Thus, visual communication design functions not merely as an aesthetic complement, but as a strategic instrument in building brand identity and expanding the market reach of MSMEs in a sustainable manner. ABSTRAK Perkembangan teknologi digital yang pesat menghadirkan tantangan baru bagi Usaha Mikro Kecil dan Menengah (UMKM) di Indonesia, khususnya dalam kemampuan beradaptasi terhadap strategi pemasaran modern. Salah satu tantangan tersebut adalah kurangnya pemahaman mengenai pentingnya branding dan komunikasi visual sebagai alat untuk membangun citra dan meningkatkan daya saing usaha. UMKM Kedai Nita, yang berlokasi di Jakarta Selatan, merupakan salah satu pelaku usaha yang belum menerapkan strategi penjenamaan secara optimal akibat keterbatasan dalam desain visual dan teknologi. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk membantu mitra dalam mengembangkan identitas merek melalui penyusunan brand guideline yang komprehensif dan sesuai dengan karakter usaha. Metode pelaksanaan kegiatan dibagi dalam tiga tahap, yaitu pra-kegiatan (audiensi dan analisis kebutuhan), pelaksanaan (pendampingan pembuatan brand guideline), serta pasca-kegiatan (evaluasi, pelaporan, dan publikasi hasil). Kegiatan ini tidak hanya memberikan solusi praktis bagi mitra, tetapi juga menjadi sarana transfer ilmu dari akademisi kepada pelaku UMKM. Diharapkan hasil kegiatan dapat meningkatkan literasi visual dan kompetensi branding UMKM, sehingga memperkuat posisi mereka dalam menghadapi persaingan pasar yang semakin kompetitif di era digital. Hasil kegiatan PKM menunjukkan bahwa penerapan elemen visual secara konsisten di berbagai media, seperti kemasan, signage, dan media digital, memberikan dampak signifikan terhadap kohesivitas merek. Dengan demikian, desain komunikasi visual bukan hanya sebagai pelengkap estetika, melainkan sebagai instrumen strategis dalam membangun merek dan memperluas jangkauan pasar UMKM secara berkelanjutan.